In patients with thoracic aortic graft infection, is graft explantation and replacement superior to in situ graft preservation?. (18th September 2021) - Poon, Shi Sum; George, Joseph; Kumar, Pankaj; Field, Mark
Summary: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether graft explantation and replacement are superior to graft preservation in patients with thoracic aortic graft infections. Altogether, more than 487 papers were found using the reported search; of these, 7 comparative studies represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers were tabulated. Although thoracic aortic graft infection is uncommon following cardiac surgery, it still carries a significant risk of in-hospital mortality and poor long-term survival. Current findings in the literature are limited to retrospective cohort studies with relatively small sample sizes; also, there is a lack of randomized controlled trials on this topic. There was significant heterogeneity in patient groups and variation in surgical techniques across centres. In this context, a graft-sparing approach may be a safe therapy with comparable early mortality and late survival outcomes in carefully selected patients. The selection may include the absence of graft pseudoaneurysm, anastomotic leak and fistula; the presence of indolent infection in patients with poor clinical conditions; and significant frailty and comorbidities where the risks of surgical explantation exceed the benefits. The rate of reinfection is low following both graft replacement and the graft-sparing approach. Moreover, the use of a tissue flap improves the surgical outcomes. Abstract : A best evidence topic was constructed according to a structured protocol.